Responding to student mental health challenges during and post-COVID-19. Issue 8 (17th November 2022) - Morris, Brenda L.; Short, Monica; Bridges, Donna; Crichton, Merrilyn; Velander, Fredrik; Rush, Emma; Iffland, Benjamin; Duncombe, Rohena
ABSTRACT: During the COVID-19 pandemic, educators around the globe seek to understand how to support students whose academic performance is impacted by mental health challenges. This article presents a co-operative inquiry undertaken by colleagues in Canada and Australia, responding to the question; what insights can the existing Carleton University framework of reflective questions offer to educators responding to student mental health challenges in social work education during the COVID-19 pandemic? The risks and complexities of attending to student mental health needs are illustrated by a pandemic-informed case study that extends the framework into this unique context and illustrates the importance of respecting learning requirements, combating discrimination, protecting students' rights, and honouring the professional and legislative mandates of social work within all responses aimed at supporting student mental health resilience during COVID-19. This article acknowledges the limitations of previous practices guiding work with students with mental health needs during any period of crisis or disaster and demonstrates that the Carleton University framework assists in developing improved processes and policy grounded in social work's commitment to social justice and critical reflection.